Pelestarian Budaya Kain Gebeng Sebagai Kearifan Lokal Palembang Melalui Perkuliahan Pendidikan IPS Mahasiswa FKIP Pendidikan Sejarah UM Palembang - Yusinta Tia Rusdiana; Heryati Heryati; Mico Mico (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2026)
This study aims to describe the preservation of Kain Gebeng culture as a local wisdom of Palembang through Social Studies Education lectures for students of the History Education Program, FKIP, Muhammadiyah University of Palembang. This research employed a descriptive qualitative method with data collection techniques consisting of observation, interviews, questionnaires, and documentation. The results showed that the community has a high level of knowledge and awareness regarding the importance of preserving Kain Gebeng as a local cultural heritage. The process of making Kain Gebeng is still carried out traditionally through weaving techniques passed down from generation to generation. In addition, the integration of Kain Gebeng into Social Studies Education lectures was able to improve students’ understanding of Palembang local culture and foster positive attitudes toward regional cultural preservation efforts. Kain Gebeng also has great potential as a local wisdom-based Social Studies learning resource because it contains historical, social, cultural, and economic values of the Palembang community. Therefore, the preservation of Kain Gebeng through education becomes a strategic effort to maintain the existence of local culture amidst the current of globalization.